2021
DOI: 10.1002/cl2.1143
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of school‐based programs to reduce bullying perpetration and victimization: An updated systematic review and meta‐analysis

Abstract: Background: Bullying first emerged as an important topic of research in the 1980s in Norway (Olweus), and a recent meta-analysis shows that these forms of aggression remain prevalent among young people globally (Modecki et al.). Prominent researchers in the field have defined bullying as any aggressive behavior that incorporates three key elements, namely: (1) an intention to harm, (2) repetitive in nature, and (3) a clear power imbalance between perpetrator and victim (Centers for Disease Control and Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 273 publications
(575 reference statements)
3
56
1
3
Order By: Relevance
“…At a practical level, these results can guide the development of intervention programs [ 24 ] aimed at all teachers to promote awareness of the issue of cyberbullying and its repercussions, both on a personal [ 25 , 26 ] and academic [ 27 ] level, as well as to work with families and parenting styles as a protective factor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a practical level, these results can guide the development of intervention programs [ 24 ] aimed at all teachers to promote awareness of the issue of cyberbullying and its repercussions, both on a personal [ 25 , 26 ] and academic [ 27 ] level, as well as to work with families and parenting styles as a protective factor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Este objetivo se acompaña de las siguientes contribuciones propias del trabajo, que intentan superar limitaciones de estudios previos: un análisis de medidas repetidas en el tiempo, tal como aconsejan los expertos (Gaffney et al, 2021a), incluyendo diferentes tipos de medidas de cambio (individual, grupal y contextual), así como diferentes tipos de información (autoinforme e iguales). Por último, el trabajo incorpora un grupo control que no pertenece al contexto del grupo de intervención (centros escolares diferentes).…”
Section: Sistemas De Apoyo Entre Igualesunclassified
“…According to Gaffney et al (2019), these inconsistent findings were associated with differences in methodological designs, types of programs, and geographical areas where the programs were implemented. A meta-analysis on the effectiveness of OBPP in Norway and the United States by Gaffney et al (2021) showed significant variations in effectiveness between the US and Norway programs. Gaffney et al (2021) found that cultural differences impacted the success of anti-bullying programs, particularly OBPP and KiVa.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis on the effectiveness of OBPP in Norway and the United States by Gaffney et al (2021) showed significant variations in effectiveness between the US and Norway programs. Gaffney et al (2021) found that cultural differences impacted the success of anti-bullying programs, particularly OBPP and KiVa. According to Gaffney et al (2021), OBPP was designed and implemented in Norway; therefore, it is not surprising that the OBPP is very effective in decreasing the number of bullying incidents in Norway, compared to the effectiveness of the program in the United States.…”
Section: Introductionmentioning
confidence: 99%